SHRIMP U–Pb zircon geochronology of the granitoids of the Imiter Inlier: Constraints on the Pan-African events in the Saghro massif, Anti-Atlas (Morocco). (February 2019) - Baidada, Bouchra; Ikenne, Moha; Barbey, Pierre; Soulaimani, Abderrahmane; Cousens, Brian; Haissen, Faouziya; Ilmen, Said; Alansari, Abdelkhalek
Abstract: This study presents new U–Pb zircon ages for three granitoid bodies in the Imiter inlier at the eastern part of the Moroccan Anti-Atlas chain, which is located in the northwestern edge of the West African Craton (WAC). Analyzes of zircon grains yield the following ages: 538 ± 6 and 575 ± 10 Ma for the Igoudrane massif, 567 ± 6 Ma for the nearby Bou Teglimt granodiorite, and 582 ± 6 Ma for the Bou Fliou granite. These new data reveal that the Igoudrane massif is younger than previously thought (677 Ma), and that all the granitoids in the Imiter area are Ediacaran in age and are related to the Ouarzazate Group. Sm-Nd isotopic data yield negative εNd(t) values (−4.5 to −0.2) and TDM model ages of 1.04–1.82 Ga. These data indicate the presence of an inherited Paleoproterozoic to Archaean component in some zircon grains and show that generation of the parent magmas involved a Neoproterozoic juvenile contribution and recycling of an older crustal component. These new data allow reinterpreting the geochemical and isotopic data of the granitoids, and revisiting the structural significance to the Igoudrane massif, which was assumed until now to be coeval with the major Pan-African event of the Central Anti-Atlas. They also bring significant constraints to discuss the context and age of deposition of the Saghro Group, which is still a matter of debate. All these data provide evidence of an emplacement of the Imiter granitoids in a subduction complex, which affected all of the Anti-Atlas chain during the Late Proterozoic time. Highlights: We provide new zircon ages for the granitoids of the Imiter inlier (Saghro, Eastern Anti-Atlas). The crystallization age of the Igoudrane massif (575 ± 10 Ma) is younger than previously thought. The granitoids in the Imiter inlier are Ediacaran to Lower Cambrian in age (538–582 Ma). An Archaean to Paleoproterozoic basement is present under the Eastern Anti-Atlas.